LITERATURE REVIEW OF FOOD TOURISM, CULINARY TOURISM AND GASTRONOMY TOURISM - Aditya Nova Putra (Bajang Institute, 2021)
This study aims to analyze the comparison of food tourism, culinary tourism and gastronomy tourism. These terminologies were heard in several times since it was related with all the activities of tourist while they were travelling to particular tourist destination. Since food has already becoming an integral part of the tourist experience itself. Food has been examined potentially integrated with destination and attraction which are all under the umbrella of hospitality industry. Theoretical foundation in this study was built based on literature review on finding definition of culinary and gastronomy based on previous studies. Comparison of tourist’s level interest has been examined in order to seek an experience in looking food and beverage during their travel. The method used is qualitative research method by describing information and data about food tourism, culinary tourism and gastronomy tourism. The technique is observation and documentation as well as library study. Data analyze from data reducing, presentation, verification and conclusion. This study will give a better understanding in the motives of people aim to experience a new thing related with local food and beverage in particular destination. Food tourism, culinary tourism, and gastronomy tourism has a similar purpose. Since food and beverage has been identified as an important role among the motivational factors to visit a destination. This could see from the people who interest to look up food and beverage, engaging with local communities and building a social connection as part of psychological needs for human being.